Orçamento base zero (obz) como instrumento de gestão - Souza, Paulo Rogério Parodi de (2008)
The budget is an indispensable tool of control and management for establishing connectivity between the various sectors of company, also acting as the element that connects strategic planning, the control of resources and the system of measures of performance and rewards. The study aims to evaluate the impacts of deploying a budget technique called Zero Base Budget (ZBB) in the cost-efficiency and in the management control process. This technique is based on identification and detailed evaluation of all activities, alternatives and costs for implementing the plans without considering the inefficiencies of past. In order to achieve the proposed objectives, a single case study was conducted using data searching and collecting information from the company web site, with the goal to complete the data bank to analyze together with the knowledgment acquired as an active observer lived at the studied company. The analysis of the results shows that the ZBB is the basis of planning one of strategic levers of the company called cost-effectiveness and provides a thorough understanding of the activities and cost facts of the company so that these are reduced in a rational way. The ZBB systematic is aligned with the values, goals and beliefs of the company that formally recognizes it as part of their culture and has the contribution of all employees who also participate individually or collectively of the budget control. It was also discovered that employees performance assessing process is related to the career development and to variable remuneration, subject to compliance with budgetary targets as a premise constraint to postulate promotions and benefits. At the end, one coud conclude that the OBZ caused a rupture capable of driving a reversal of undesirable results, contributing effectively as a tool of management control and becoming a model of budgetary control in the analyzed company's units abroad.